2017
DOI: 10.1177/1010428317716501
|View full text |Cite
|
Sign up to set email alerts
|

Balaglitazone reverses P-glycoprotein-mediated multidrug resistance via upregulation of PTEN in a PPARγ-dependent manner in leukemia cells

Abstract: Multidrug resistance in tumor cells is still a big challenge in cancer treatment. Therefore, identification ofsafe and effective multidrug resistance-reversing compounds with minimal side effects is an important approach in cancer treatment. Here, we investigated the role and potential mechanisms of peroxisome proliferator-activated receptor γ in doxorubicin-resistant human myelogenous leukemia (K562/DOX) cells. The effect of doxorubicin on cell viability following treatment with balaglitazone, a peroxisome pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…[86] In another study, they reported that in estrogen receptor (ER)-positive MCF7 cells, antiproliferative effect of troglitazone is associated with decreased activity of histone deacetylase (HDAC), increased histone 3 (H3) lysine 9 (H3K9) and H3K23 acetylation, H2AX and H3S10 phosphorylation, and H3K79 mono-and di-methylation. [75,92,93] Beneficial effects of TZDs in hematologic malignancies have been reported in many previous studies [94][95][96][97][98] and investigations of our department. They also suggested that inhibition of PI3K signaling pathway may be involved in cell killing of troglitazone.…”
Section: Thiazolidinedionesmentioning
confidence: 67%
See 1 more Smart Citation
“…[86] In another study, they reported that in estrogen receptor (ER)-positive MCF7 cells, antiproliferative effect of troglitazone is associated with decreased activity of histone deacetylase (HDAC), increased histone 3 (H3) lysine 9 (H3K9) and H3K23 acetylation, H2AX and H3S10 phosphorylation, and H3K79 mono-and di-methylation. [75,92,93] Beneficial effects of TZDs in hematologic malignancies have been reported in many previous studies [94][95][96][97][98] and investigations of our department. They also suggested that inhibition of PI3K signaling pathway may be involved in cell killing of troglitazone.…”
Section: Thiazolidinedionesmentioning
confidence: 67%
“…They also suggested that inhibition of PI3K signaling pathway may be involved in cell killing of troglitazone. [99] Furthermore, our unpublished data showed that balaglitazone, another member of TZDs, reduced P-gp expression and reversed MDR by upregulating PTEN expression in K562/ Dox cells. [87] PPARγ has been reported to be overexpressed in renal cancer cells, and treatment with TZDs inhibits cell proliferation through arresting cells at G0/G1 phase and induces apoptosis by downregulating the antiapoptotic Bcl-2 protein and upregulating proapoptotic Bax protein.…”
Section: Thiazolidinedionesmentioning
confidence: 94%
“…A number of NF‐κB regulated lncRNAs have been reported, which can impact cellular processes. The abnormal regulation of NF‐κB and its downstream targets often leads to inflammation, drug resistance, and metastasis in breast cancer (Majidinia et al, 2017; Yousefi et al, 2017). Several studies have exposed the role of NF‐κB interaction with lncRNA (NKILA) in the NF‐κB signaling pathway (Figure 1).…”
Section: Crosstalk Between Various Signaling Pathways and Lncrnasmentioning
confidence: 99%
“…For cell viability analysis, MTT assay was performed as described previously . In brief, MCF‐7 and MCF‐7/DOX cells were seeded in triplicate into 96‐well flat‐bottomed plates in RPMI‐1640 medium with 10% FBS at the density of 10 4 cells/well and incubated for 24 hr in 37°C with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The possible application of antidiabetic drugs (biguanides, thiazolidinediones, sulfonyl ureas) in cancer treatment has been reviewed in our very recent study . In another study, we showed that troglitazone, an oral antidiabetic belonging to thiazolidinedione family of drugs, enhanced the cytotoxicity of doxorubicin (DOX) in resistant chronic myeloid leukemia (CML) cells via downregulation of P‐gp expression . In this study, our aim is to investigate the possible effects of metformin as a widely used oral antidiabetic drug on the cytotoxicity of DOX, a P‐gp substrate, and P‐gp expression as well as its activity on the DOX‐resistant breast cancer cells (MCF‐7/DOX).…”
Section: Introductionmentioning
confidence: 99%